Physics : the First Science. - Lindenfeld, Peter; Brahmia, Suzanne White, 1963- (Rutgers University Press, 2011)
Today's physics textbooks have become encyclopedic, offering students dry discussions, rote formulas, and exercises with little relation to the real world. Physics: The First Science offers uniquely accessible, student-friendly explanations, historical and philosophical perspectives and mathematics in easy-to-comprehend dialogue. It emphasizes the unity of physics and its place as the basis for all science. With their experience instructing both students and teachers of physics for decades, Peter Lindenfeld and Suzanne White Brahmia have developed an algebra-based physics book with fea.
Keywords: Physics -- Textbooks.; SCIENCE -- Energy.; SCIENCE -- Mechanics -- General.; SCIENCE -- Physics -- General.; Physics; Textbooks